The Effect of Long-Acting Methylphenidate and Modafinil on Attention and Impulsivity of Children with ADHD using a Continuous Performance Test: A Comparative Study - Zahed, Ghazal; roozbakhsh, malihe; Davari Ashtiani, Rozita; Razjouyan, Katayoun (Iranian Journal of Child Neurology, 2022)
Objectives Given the importance of having a continuous performance for the academic and social life of children with attention-deficit/hyperactivity disorder (ADHD), in this study, a continuous performance test was used to compare the effect of long-acting methylphenidate and modafinil on attention and impulsivity of these children. Materials & Methods A randomized clinical trial was conducted on 50 children aged 6 to 12 years with ADHD in the child and adolescent psychiatric departments of Imam Hossein and Mofid hospitals, Tehran, Iran. The children were selected by availability sampling and randomly divided into two groups of 25. One group was treated with long-acting methylphenidate and the other with modafinil for 14 days. The continuous performance test was carried out before and after the treatment. The obtained data were analyzed by F and t tests Results Long-acting methylphenidate and modafinil were both effective in improving attention and impulsivity in children with ADHD. There was no significant difference between the two drugs in terms of effectiveness on attention and impulsivity. Conclusion The findings of this study showed that long-acting methylphenidate and modafinil are equally effective in improving attention and impulsivity in children aged 6 to 12 years with ADHD.